2017
DOI: 10.1371/journal.pone.0180653
|View full text |Cite
|
Sign up to set email alerts
|

A new analysis of heart rate variability in the assessment of fetal parasympathetic activity: An experimental study in a fetal sheep model

Abstract: Analysis of heart rate variability (HRV) is a recognized tool in the assessment of autonomic nervous system (ANS) activity. Indeed, both time and spectral analysis techniques enable us to obtain indexes that are related to the way the ANS regulates the heart rate. However, these techniques are limited in terms of the lack of thresholds of the numerical indexes, which is primarily due to high inter-subject variability. We proposed a new fetal HRV analysis method related to the parasympathetic activity of the AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 16 publications
1
30
0
3
Order By: Relevance
“…We developed a new index, the FSI, based on our previous work in adults and newborns. We demonstrated that the FSI was associated with lower interindividual variability and a higher effect size than commonly used HRV analysis methods, suggesting that the index could better detect a decrease in parasympathetic tone . In a preliminary study, we showed a correlation between the FSI and fetal acidosis in a continuous occlusion model, demonstrating proof of concept for the FSI.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We developed a new index, the FSI, based on our previous work in adults and newborns. We demonstrated that the FSI was associated with lower interindividual variability and a higher effect size than commonly used HRV analysis methods, suggesting that the index could better detect a decrease in parasympathetic tone . In a preliminary study, we showed a correlation between the FSI and fetal acidosis in a continuous occlusion model, demonstrating proof of concept for the FSI.…”
Section: Discussionmentioning
confidence: 61%
“…Our team proposes a new index, the fetal stress index (FSI), based on an original method of HRV analysis combining spectral and time domain analyses. In a previous experimental study, we showed that this index was sensitive and specific for fluctuations of parasympathetic nervous system activity and had lower interindividual variability and a higher ability to detect changes in parasympathetic nervous system activity compared with commonly used methods of measuring HRV . We also demonstrated that this index was correlated with fetal pH …”
Section: Introductionmentioning
confidence: 60%
“…Eleven near-term pregnant sheep (128 +/- 2 days gestational age, term = 145 days) underwent surgical procedure. Anesthetics and surgical techniques protocols followed those previously described by our team or in the literature [ 14 16 ]. Pregnant Charmoise sheep (INRA, Leudeville, France) were fasted 24 h before surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Our hypothesis is that, because of its reflecting parasympathetic activity, it makes it possible to detect fetuses at risk of acidosis. In a previous study, we shown that this index had a lower inter-subject variability, and a higher effect size compared to other HRV analysis methods [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative and quantitative changes in anatomical structure and physiological function are the basis of disease research, so accurate descriptions of baseline properties are essential. Numerous reports have examined normal parameters for blood, heart, brain, liver, kidney, and other large organs among common experimental model animals [1][2][3][4][5], but few have examined eye structure and function in different models for ophthalmology research. A complete set of anatomic and physiological parameters for speci c experimental animals will be invaluable for choosing the optimal model, preparation technique, and measurement technology.…”
Section: Introductionmentioning
confidence: 99%